High-storage EPE adhesive film, preparation method thereof and photovoltaic module
By designing a multi-layer structure in the EPE film and adding specific raw materials, the problem of degradation of the bonding performance of the EPE film after long-term storage is solved, and the good bonding performance of the high-storage EPE film and the reliability of the photovoltaic module are improved.
Patent Information
- Application Number
- CN202311384737.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-24
- Publication Date
- 2025-04-29
AI Technical Summary
After the existing EPE composite packaging film is placed for too long, the initial adhesion force to the glass/backplane is reduced, resulting in lower reliability of the photovoltaic module.
A high-storage EPE film consisting of the first EVA layer, POE layer and the second EVA layer stacked in sequence along the thickness direction is used. By adding raw materials such as silane adhesive grafting and crosslinking agent to the EVA layer and the POE layer, the film still maintains good bonding performance after long-term storage.
The high-storage EPE film has achieved good bonding performance in initial and aging, delaying the aging of the film, and improving the service life and reliability of photovoltaic modules.
Smart Images

Figure CN119899598A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photovoltaic cells, and in particular to a high-storage EPE adhesive film, a preparation method thereof and a photovoltaic module. Background Art
[0002] In the related technology, P-type batteries have already achieved stable mass production, and N-type batteries have also been partially mass-produced; encapsulation films are roughly divided into three categories: ethylene-vinyl acetate copolymer (EVA), ethylene and butene polymer or ethylene and octene polymer (POE), and composite films that take into account POE film and EVA film. Referred to as (EPE), EVA encapsulation film has excellent adhesion to glass and backplane, but has the defects of high water permeability and high resistance; although POE encapsulation film has low water permeability and low resistance, it has poor adhesion to glass / backplane during long-term use; the existing EPE composite encapsulation film is relatively low in price, but when the EPE composite encapsulation film is placed for too long (more than 3 months), the initial adhesion to the glass / backplane will decrease, and the reliability of the photovoltaic module is relatively low. In view of this, it is necessary to develop a high-storage EPE encapsulation film. Summary of the invention
[0003] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, one object of the present invention is to provide a high storage type EPE adhesive film with good initial and after aging adhesive properties.
[0004] Another object of the present invention is to provide a method for preparing a high storage type EPE film.
[0005] Another object of the present invention is to provide a photovoltaic module.
[0006] According to an embodiment of the first aspect of the present invention, the present invention provides a high storage type EPE film, comprising: a first EVA layer, a POE layer and a second EVA layer stacked in sequence along the thickness direction; the first EVA layer comprises raw materials and their weight proportions are as follows: 70 to 75 parts of EVA particles, 20 to 25 parts of silane tackifier grafted EVA granules, 0.5 to 1 part of a cross-linking agent, 0.4 to 1 part of a co-cross-linking agent, 0.7 to 1.5 parts of an acrylate, 0.1 to 0.5 parts of a low molecular weight tackifier and 0.05 to 0.3 parts of a light stabilizer; and / or the second EVA The layer includes raw materials and their weight proportions are as follows: 70-75 parts of EVA particles, 20-25 parts of silane thickener grafted EVA granules, 0.5-1 parts of cross-linking agent, 0.4-1 parts of auxiliary cross-linking agent, 0.7-1.5 parts of acrylate, 0.1-0.5 parts of low molecular weight thickener and 0.05-0.3 parts of light stabilizer; wherein the structure of the silane thickener is shown in the following formula I: (I) YR-SiX3, wherein Y is an active group participating in free radical reaction, R is a linear hydrophobic carbon chain, the number of carbon atoms in the carbon chain is 5-8, and SiX3 is siloxane.
[0007] According to the high storage type EPE adhesive film of the present invention, the high storage type EPE adhesive film 100 according to a specific embodiment of the present invention includes a first EVA layer, a POE layer and a second EVA layer, which can provide triple high barrier to water vapor, reduce silane hydrolysis, and ensure initial and after-aging adhesion.
[0008] According to some embodiments of the present invention, the silane adhesion promoter includes: at least one of γ-methacryloxypentyltrimethoxysilane, γ-methacryloxyhexyltrimethoxysilane, γ-methacryloxyheptyltrimethoxysilane, 3-(methacryloxy)pentyltriethoxysilane, 3-(methacryloxy)hexyltriethoxysilane, 3-(methacryloxy)heptyltriethoxysilane, vinylpentyltrimethoxysilane, vinylhexyltrimethoxysilane and vinylheptyltrimethoxysilane.
[0009] According to some embodiments of the present invention, the preparation method of the silane tackifier grafted EVA granules is as follows: the initiator, the catalyst, the silane tackifier and the EVA particles are measured, fully mixed and absorbed, and then added, extruded, uniformly sheared, and cooled to obtain the finished product.
[0010] According to some embodiments of the present invention, the POE layer includes raw materials and their weight parts are as follows: 70-80 parts of POE particles, 20-30 parts of silane thickener grafted POE granules, 0.5-1.2 parts of cross-linking agent, 0.6-1 parts of auxiliary cross-linking agent, 0.2-0.5 parts of acrylate, 0.2-0.5 parts of low molecular weight thickener, 0.05-0.2 parts of silane thickener and 0.05-0.2 parts of light stabilizer.
[0011] According to some embodiments of the present invention, the preparation method of the silane-silane thickener grafted POE granules is as follows: the initiator, catalyst, silane thickener and the POE particles are measured, fully mixed and absorbed, and then added, extruded, uniformly sheared, and cooled to obtain the finished product.
[0012] According to some embodiments of the present invention, the crosslinking agent is one or more of tert-butyl peroxy-2-ethylhexyl carbonate, tert-amyl peroxy-2-ethylhexyl carbonate, methyl ethyl ketone peroxide, benzoyl peroxide, di-tert-butyl peroxide and diisopropylbenzene hydroperoxide.
[0013] According to some embodiments of the present invention, the auxiliary cross-linking agent is one or more of triallyl isocyanurate, triallyl cyanurate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, tripropylene glycol diacrylate, dipropylene glycol diacrylate and triethylene glycol methyl diacrylate.
[0014] According to some embodiments of the present invention, the low molecular adhesive is one or more of γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, 3-(methacryloxy)propyltriethoxysilane, 3-(methacryloxy)propyltrimethoxysilane, vinyltrimethoxysilane, and vinyltriethoxysilane.
[0015] According to some embodiments of the present invention, the thickness of the first EVA layer is d1, wherein d1 satisfies: 200μm≤d1≤220μm; and / or the thickness of the POE layer is d2, wherein d2 satisfies: 190μm≤d2≤210μm; and / or the thickness of the second EVA layer is d3, wherein d3 satisfies: 200μm≤d3≤220μm.
[0016] According to an embodiment of the second aspect of the present invention, the present invention provides a method for preparing a high-storage EPE film according to an embodiment of the first aspect of the present invention, comprising the following steps: mixing the raw materials of the first EVA layer, the POE layer and the second EVA layer respectively, letting them stand, taking the mixed mixture and extruding it into a composite molten film through a twin-screw and double-die cast extrusion, and cooling and molding.
[0017] According to an embodiment of the third aspect of the present invention, the present invention provides a photovoltaic module, comprising: a front cover plate, a front packaging film, a battery layer, a back packaging film and a back cover plate stacked in sequence along the thickness direction; at least one of the front packaging film and the back packaging film is the high-storage type EPE film described in the embodiment of the first aspect of the present invention, or the high-storage type EPE film prepared by the preparation method described in the embodiment of the second aspect of the present invention.
[0018] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0020] Figure 1 It is a schematic structural diagram of a high storage type EPE film according to an embodiment of the present invention.
[0021] Reference numerals:
[0022] 100: High storage type EPE film;
[0023] 1: first EVA layer; 2: POE layer; 3: second EVA layer. DETAILED DESCRIPTION
[0024] The embodiments of the present invention are described in detail below. The embodiments described with reference to the accompanying drawings are exemplary. Figure 1 A high storage type EPE adhesive film 100 according to a specific embodiment of the present invention is described.
[0025] like Figure 1 As shown, the high storage type EPE film 100 of the specific embodiment of the present invention includes a first EVA layer 1 , a POE layer 2 and a second EVA layer 3 .
[0026] Among them, the first EVA layer 1, the POE layer 2 and the second EVA layer 3 are stacked in sequence along the thickness direction. In this way, the first EVA layer 1 and the second EVA layer 3 of the high storage type EPE adhesive film 100 of the specific embodiment of the present invention are respectively placed on both sides of the thickness direction of the POE layer 2. In this way, when forming a photovoltaic module, the first EVA layer 1 and the second EVA layer 3 are respectively in contact with other photovoltaic modules, which can fully ensure the bonding strength between the high storage type EPE adhesive film 100 of the specific embodiment of the present invention and other modules.
[0027] Further, the first EVA layer 1 includes raw materials and their weight proportions as follows: 70-75 parts of EVA particles, 20-25 parts of silane tackifier grafted EVA granules, 0.5-1 parts of crosslinking agent, 0.4-1 parts of auxiliary crosslinking agent, 0.7-1.5 parts of acrylate, 0.1-0.5 parts of low molecular weight tackifier and 0.05-0.3 parts of light stabilizer. In this way, the first EVA layer 1 is used in combination with EVA particles, silane tackifier grafted EVA granules, crosslinking agent, auxiliary crosslinking agent, etc. The silane tackifier grafted EVA granules not only ensure the bonding stability of the first EVA layer 1 after long-term storage, so that the first EVA layer 1 has a greater bonding strength with the backboard, but also ensures hydrophobic properties. The low molecular weight tackifier ensures the conventional bonding performance of the first EVA layer 1. In this way, it can be ensured that the bonding performance and other use performance of the high storage type EPE adhesive film 100 are reliable during regular use and after long-term storage. For example, it can be ensured that the high storage type EPE adhesive film 100 of the present invention still has good adhesive properties after being stored for 3 months. Thus, the aging of the first EVA layer 1 is delayed, and the adhesive properties of the high storage type EPE adhesive film 100 after long-term storage are ensured. In addition, in the first EVA layer 1, the amount of silane tackifier grafted EVA granules added is appropriate. When the amount added is less than 20 parts, the adhesive properties of the high storage type EPE adhesive film 100 of the present invention after long-term storage will be poor; when the amount added is more than 25 parts, the cost of the high storage type EPE adhesive film 100 of the present invention will increase.
[0028] Furthermore, the second EVA layer 3 includes raw materials and their weight proportions as follows: 70-75 parts of EVA particles, 20-25 parts of silane grafted EVA granules, 0.5-1 parts of crosslinking agents, 0.4-1 parts of auxiliary crosslinking agents, 0.7-1.5 parts of acrylates, 0.1-0.5 parts of low molecular weight tackifiers and 0.05-0.3 parts of light stabilizers. In this way, the second EVA layer 3 uses EVA particles, silane tackifier grafted EVA granules and crosslinking agents, auxiliary crosslinking agents, low molecular weight tackifiers, etc. The silane tackifier grafted EVA granules not only ensure the bonding stability of the second EVA layer 3 after long-term storage, so that the second EVA layer 3 has a greater bonding strength with the backboard, but also ensures hydrophobic properties. The low molecular weight tackifier ensures the conventional bonding properties of the second EVA layer 3. In this way, it can be ensured that the adhesive performance and other performance of the high storage type EPE adhesive film 100 are reliable during normal use and after long-term storage. For example, it can be ensured that the high storage type EPE adhesive film 100 of the present invention still has good adhesive performance after being stored for 3 months. In this way, the aging of the second EVA layer 3 is delayed, and the adhesive performance of the high storage type EPE adhesive film 100 after long-term storage is guaranteed.
[0029] Furthermore, the structure of the silane adhesion promoter is shown in the following formula I: (I) YR-SiX3, wherein Y is an active group participating in a free radical reaction, R is a linear hydrophobic carbon chain, the number of carbon atoms in the carbon chain is 5 to 8, and SiX3 is a siloxane suitable for substrate bonding. In this way, the carbon chain length of the silane adhesion promoter is relatively long, and it is not easy to decompose during long-term storage, which is conducive to maintaining the bonding performance of the first EVA layer 1 and / or the second EVA layer 3 after long-term storage.
[0030] According to the high storage type EPE film 100 of the specific embodiment of the present invention, including the first EVA layer 1, the POE layer 2 and the second EVA layer 3, it can be triple high barrier water vapor, reduce silane hydrolysis, and ensure the initial and aging adhesion. Specifically, by adding EVA particles, silane tackifier grafted EVA granules and cross-linking agents, auxiliary cross-linking agents, low molecular tackifiers, etc. to the first EVA layer 1 and / or the second EVA layer 3, the silane tackifier grafted EVA granules can ensure the adhesion stability of the first EVA layer 1 and / or the second EVA layer 3 after long-term storage, so that the first EVA layer 1 and / or the second EVA layer 3 have a greater bonding strength with the backboard, and the hydrophobic property is ensured. The low molecular tackifier ensures the conventional bonding performance of the second EVA layer 3. In this way, it can be ensured that the bonding performance and other use performance of the high storage type EPE film 100 are reliable during conventional use and after long-term storage. For example, it can be ensured that the high storage type EPE adhesive film 100 of the present invention still has good adhesive performance after being stored for 3 months, thereby delaying the aging of the first EVA layer 1 and / or the second EVA layer 3, and ensuring the adhesive performance of the high storage type EPE adhesive film 100 after long-term storage.
[0031] According to some embodiments of the present invention, the silane adhesion promoter includes at least one of γ-methacryloxypentyltrimethoxysilane, γ-methacryloxyhexyltrimethoxysilane, γ-methacryloxyheptyltrimethoxysilane, 3-(methacryloxy)pentyltriethoxysilane, 3-(methacryloxy)hexyltriethoxysilane, 3-(methacryloxy)heptyltriethoxysilane, vinylpentyltrimethoxysilane, vinylhexyltrimethoxysilane and vinylheptyltrimethoxysilane. With such a configuration, the selection of the silane adhesion promoter is diverse.
[0032] According to some embodiments of the present invention, the preparation method of silane tackifier grafted EVA granules is as follows: after the initiator, catalyst, silane tackifier and EVA particles are metered, fully mixed and absorbed, the materials are added, extruded, and uniformly sheared. After cooling, the finished product is obtained. In this way, the silane tackifier grafted EVA granules obtained after the grafting reaction of the silane tackifier and the EVA particles are more stable than the EVA particle structure, slowly decompose after long-term storage, and the EVA particles and silane tackifier are obtained again after decomposition. EVA particles and silane tackifiers can continue to be used as raw materials for the first EVA layer 1 and / or the second EVA layer 3. Thereby extending the service life of the first EVA layer 1 and / or the second EVA layer 3. Wherein, the initiator can be a peroxide initiator. Specifically, with reference to the type of crosslinking agent and the copolymerization catalyst of the present invention, it is a copolymerization catalyst, such as α-olefins, conjugated dienes, etc. The initiator, catalyst, silane thickener and EVA particles are put into a special device metering equipment, and after being fully mixed and absorbed, they are fed into an extruder through a metering pump according to the following weight ratio: initiator: catalyst: silane thickener: EVA particles = 0.5-1: 0.05-0.1: 1-3: 95-98. The grafted material is evenly sheared by a high shear device, and the finished product is obtained after cooling.
[0033] According to some embodiments of the present invention, the POE layer 2 includes the following raw materials and weight parts: 70-80 parts of POE particles, 20-30 parts of silane tackifier grafted POE granules, 0.5-1.2 parts of crosslinking agent, 0.6-1 parts of auxiliary crosslinking agent, 0.2-0.5 parts of acrylate, 0.2-0.5 parts of low molecular weight tackifier, 0.05-0.2 parts of silane tackifier and 0.05-0.2 parts of light stabilizer. In this way, the POE layer 2 is used in combination with POE particles, silane tackifier grafted POE granules and crosslinking agents, auxiliary crosslinking agents, low molecular weight tackifiers, silane tackifiers, etc. The silane tackifier grafted POE granules and the silane tackifier cooperate synergistically, which not only ensures the bonding stability of the POE layer 2 after long-term storage, so that the POE layer 2 has a greater bonding strength with the backplane, but also ensures hydrophobic properties. The low molecular weight tackifier ensures the conventional bonding properties of the POE layer 2. In this way, it can be ensured that the adhesive properties and other performance properties of the high storage type EPE film 100 are reliable during normal use and after long-term storage. For example, it can be ensured that the high storage type EPE film 100 of the present invention still has good adhesive properties after being stored for 3 months. Thereby delaying the aging of the POE layer 2, and ensuring the adhesive properties of the high storage type EPE film 100 after long-term storage. Furthermore, compared with the first EVA layer 1 and the second EVA layer 3, the raw materials of the POE layer 2 reduce the amount of low molecular weight thickeners added, and add silane thickeners. The silane thickener can hydrophobically modify the POE particles, improve the compatibility between the POE particles and the additives in the POE layer 2, and promote the cross-linking reaction of the POE particles. Adding silane thickeners to the POE layer 2 grafted with POE granules can improve the hydrophobic properties of the POE layer 2 film. The amount of cross-linking agent added in the POE layer 2 is reduced, and the compatibility between the POE particles and the silane additives is further improved. The amount of the co-crosslinking agent added in POE layer 2 is increased to compensate for the risk of reduced crosslinking strength due to the reduction of the crosslinking agent.
[0034] According to some embodiments of the present invention, the preparation method of POE granulation material grafted with silane silane tackifier is as follows: after the initiator, catalyst, silane tackifier and POE particles are metered, fully mixed and absorbed, the materials are added, extruded, uniformly sheared, and cooled to obtain the finished product. In this way, the silane tackifier grafted POE granulation material obtained after the grafting reaction of the silane tackifier and the POE particles is more stable than the POE particle structure, slowly decomposes after long-term storage, and the POE particles and silane tackifier are obtained again after decomposition. POE particles and silane tackifiers can continue to be used as raw materials for POE layer 2. Thereby extending the service life of the first POE layer 2. Among them, the initiator can be a peroxide initiator. Specifically, with reference to the type of crosslinking agent and copolymerization catalyst of the present invention, it is a copolymerization catalyst, such as α-olefins, conjugated dienes, etc. The initiator, catalyst, silane thickener and POE particles are placed in a special device metering equipment. After being fully mixed and absorbed, they are added to the extruder through a metering pump according to the following weight ratio: initiator: catalyst: silane thickener: POE particles = 0.5-1: 0.05-0.1: 1-3: 95-98. The grafted material is evenly sheared by a high shear device, and after cooling, the POE layer film is obtained.
[0035] According to some embodiments of the present invention, the crosslinking agent is one or more of tert-butyl peroxide-2-ethylhexyl carbonate, tert-amyl peroxy-2-ethylhexyl carbonate, methyl ethyl ketone peroxide, benzoyl peroxide, di-tert-butyl peroxide and diisopropylbenzene hydroperoxide. In this way, the crosslinking agent and the auxiliary crosslinking agent can induce a crosslinking reaction between the raw materials. For example, a crosslinking reaction between EVA particles is induced, a crosslinking reaction between POE particles is induced, and the like.
[0036] According to some embodiments of the present invention, the auxiliary cross-linking agent is one or more of triallyl isocyanurate, triallyl cyanurate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, tripropylene glycol diacrylate, dipropylene glycol diacrylate and triethylene glycol methyl diacrylate. The auxiliary cross-linking agent acts synergistically with the cross-linking agent to promote the cross-linking reaction between the raw material particles.
[0037] According to some embodiments of the present invention, the low molecular adhesive is one or more of: γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, 3-(methacryloxy)propyltriethoxysilane, 3-(methacryloxy)propyltrimethoxysilane, vinyltrimethoxysilane, and vinyltriethoxysilane. In this way, the low molecular adhesive has strong bonding properties and can ensure the bonding properties of the first EVA layer 1 and / or the POE layer 2 and / or the second EVA layer 3 under normal conditions. However, due to the short carbon chain, the low molecular tackifier is easily decomposed after long-term storage, thereby losing its bonding properties.
[0038] According to some embodiments of the present invention, the acrylate is at least one of trimethylol propane triacrylate, trimethylol propane triacrylate, pentaerythritol tetraacrylate, polyethylene glycol diacrylate and tricyclohexane dimethanol diacrylate. Such an arrangement further promotes the cross-linking reaction between the raw materials.
[0039] According to some embodiments of the present invention, the light stabilizer is at least one of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate, bis-2,2,6,6-tetramethylpiperidinol sebacate or hindered amine light stabilizer, 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-hydroxybenzyl) benzene, tris(2,4-di-tert-butylphenyl) phosphite and 2,2,6,6-tetramethyl-4-piperidinyl ester. In this way, the light stability of the first EVA layer 1 and / or the POE layer 2 and / or the second EVA layer 3 can be increased.
[0040] According to some embodiments of the present invention, the thickness of the first EVA layer 1 is d1, wherein d1 satisfies: 200μm≤d1≤220μm. In this way, when d1 is less than 200μm, the thickness of the first EVA layer 1 is small, and the adhesive performance of the high storage type EPE adhesive film 100 of the present invention may be poor; when d1 is greater than 220μm, the thickness of the first EVA layer 1 is large, and the water permeability of the high storage type EPE adhesive film 100 of the present invention may be poor. By setting d1 to satisfy 200μm≤d1≤220μm, the thickness of the first EVA layer 1 is appropriate, and the high storage type EPE adhesive film 100 of the present invention has good water permeability and reliable adhesion.
[0041] According to some other embodiments of the present invention, the thickness of the POE layer 2 is d2, wherein d2 satisfies: 190μm≤d2≤210μm. In this way, when d2 is less than 190μm, the thickness of the POE layer 2 is small, and the water permeability of the high storage type EPE adhesive film 100 of the present invention may be poor; when d2 is greater than 1900μm, the thickness of the POE layer 2 is large, and the bonding performance of the high storage type EPE adhesive film 100 of the present invention may be poor. By setting d2 to satisfy 190μm≤d3≤210μm, the thickness of the POE layer 2 is appropriate, and the high storage type EPE adhesive film 100 of the present invention has good water permeability and reliable adhesion.
[0042] According to some other embodiments of the present invention, the thickness of the second EVA layer 3 is d3, wherein d3 satisfies: 200μm≤d3≤220μm. In this way, when d3 is less than 200μm, the thickness of the second EVA layer 3 is small, and the bonding performance of the high storage type EPE adhesive film 100 of the present invention may be poor; when d3 is greater than 220μm, the thickness of the second EVA layer 3 is large, and the water permeability of the high storage type EPE adhesive film 100 of the present invention may be poor. By setting d3 to satisfy 200μm≤d3≤220μm, the thickness of the second EVA layer 3 is appropriate, and the high storage type EPE adhesive film 100 of the present invention has good water permeability and reliable adhesion.
[0043] According to an embodiment of the second aspect of the present invention, the present invention provides a method for preparing a high-storage EPE film 100 according to an embodiment of the first aspect of the present invention, comprising the following steps: mixing the raw materials of the first EVA layer 1, the POE layer 2 and the second EVA layer 3 respectively, letting them stand, taking the mixed mixture and extruding it into a composite molten film through a twin-screw and double-die cast extrusion, and cooling and molding. Taking the first EVA layer 1 as an example, 70-75 parts of EVA particles, 20-25 parts of silane thickener grafted EVA granules, 0.5-1 parts of crosslinking agent, 0.4-1 parts of auxiliary crosslinking agent, 0.7-1.5 parts of acrylate, 0.1-0.5 parts of low molecular weight thickener and 0.05-0.3 parts of light stabilizer are stirred evenly in a mixer, mixed in a closed container and allowed to stand for a period of time, and then the mixture is extracted and extruded into a composite molten film through a twin-screw and twin-die cast film on a film production line, and then cooled by multiple cooling rollers, trimmed and collected into a roll-shaped finished product; the thickness of the first EVA layer 1 is controlled at 200-220 microns.
[0044] According to the preparation method of the high storage type EPE adhesive film 100 of the present invention, the raw materials are mixed to make the raw material particles undergo a cross-linking reaction, and then the first EVA layer 1, the POE layer 2 and the second EVA layer 3 of the high storage type EPE adhesive film 100 of the present invention are obtained by extrusion molding. The preparation method is simple and easy to operate.
[0045] According to an embodiment of the second aspect of the present invention, the present invention provides a photovoltaic module, comprising: a front cover plate, a front packaging film, a battery layer, a back packaging film and a back cover plate stacked in sequence along the thickness direction; at least one of the front packaging film and the back packaging film is a high-storage type EPE film 100 according to an embodiment of the first aspect of the present invention, or a high-storage type EPE film 100 prepared by the preparation method of an embodiment of the second aspect of the present invention.
[0046] According to the photovoltaic module of the present invention, the front packaging film and / or the back packaging film have reliable adhesion and good water permeability under normal conditions and after long-term storage, so the photovoltaic module has a long service life.
[0047] Specific exemplary embodiments
[0048] Comparative Example 1-Comparative Example 3, Example 1-Example 6
[0049] The EPE films of Comparative Examples 1 to 3 and the high storage EPE films of Specific Examples 1 to 6 of the present invention include a first EVA layer, a POE layer, and a second EVA layer stacked in sequence along the thickness direction. The raw materials and weight proportions of the first EVA layer, the second EVA layer, and the POE layer are shown in the following embodiments:
[0050] The preparation method of the silane tackifier grafted EVA / POE granules is as follows: the initiator, catalyst, silane tackifier and EVA particles are measured, fully mixed and absorbed, added, extruded, uniformly sheared, and cooled to obtain the finished product. The weight ratio of initiator: catalyst: silane tackifier: EVA particles / POE particles is 0.5: 0.05: 1: 95.
[0051] The preparation method comprises the following steps: mixing the raw materials of the first EVA layer 1, the POE layer 2 and the second EVA layer 3 respectively, letting them stand, taking the mixed materials and extruding them into a composite molten rubber film through a twin-screw and twin-die casting, and cooling and molding them.
[0052] Comparative Example 1
[0053]
[0054]
[0055] Example 1
[0056]
[0057] Comparative Example 2
[0058]
[0059] Comparative Example 3
[0060]
[0061]
[0062] Example 2
[0063]
[0064] Example 3
[0065]
[0066]
[0067] Example 4
[0068]
[0069] Example 5
[0070]
[0071]
[0072] Example 6
[0073]
[0074] Performance Testing
[0075] The thickness of each layer of the EPE film obtained in the above Comparative Examples 1 to 3 and Examples 1 to 6 was set to 200 μm, 190 μm and 200 μm for the first EVA layer, POE layer and the second EVA layer, respectively.
[0076] The performance tests of the EPE films obtained in Comparative Examples 1 to 3 and Examples 1 to 6 are as follows:
[0077] 1. Comparison of initial vulcanization and cross-linking degree. The vulcanization test method refers to GB / T 16584-1996, and the cross-linking test method refers to Q / HZF001-2013 for sample preparation and testing.
[0078] Table 1. Comparison of initial vulcanization and crosslinking degree of EPE films obtained in Comparative Examples 1-3 and Examples 1-6
[0079]
[0080]
[0081] Combined with the specific embodiments and comparative examples and test data, comparative example 1 is a conventional EPE film, and comparative examples 2-3 and examples 1-6 are improvements on conventional EPE films in different ways. Comparing the test results in Table 1, it can be seen that there is no substantial difference in the vulcanization data of the encapsulation films of comparative examples 1-3 and the high storage EPE films of examples 1-6. It can be preliminarily determined that the improved EPE processing performance and crosslinking time are no problem and will not affect the initial performance of the film; from the perspective of crosslinking degree, although comparative example 3 is the lowest, it meets the crosslinking degree requirements of the EPE film. Even if the amount of crosslinking agent added in the POE layer is reduced, it will not affect the overall crosslinking performance of the EPE film of the present invention.
[0082] 2. At room temperature, the initial peel force and the peel strength after being placed at a constant temperature for different lengths of time, the initial peel force after DH2000 and the peel strength after being placed at a constant temperature for different lengths of time (between glass).
[0083] The test method for peel strength is carried out in accordance with GB / T 2790-1995 for sample preparation and testing.
[0084] Table 2. Initial and post-aging peel strength tests of the EPE films obtained from Comparative Examples 1-3 and Examples 1-6
[0085]
[0086]
[0087] In order to meet the use needs of the packaging film under different operating conditions, the peel strength needs to meet the following requirements: initial peel strength> 120N / cm, peel strength after DH2000> 100N / cm.
[0088] Combining the test data of Comparative Examples 1 to 3, Examples 1 to 6, and Tables 1 and 2 of the present invention, it can be seen that the initial peel strength of Comparative Example 1, i.e. conventional EPE, is greatly reduced after being placed at room temperature for 3 months. The reason is that the silane in the film is partially hydrolyzed, resulting in a decrease in adhesion; when the POE layer is added with a silane tackifier grafted material and a silane tackifier, or the amount of cross-linking agent added is appropriately reduced (such as Comparative Examples 2 and 3), after being placed at room temperature for 3 months, the initial DH2000 can ensure that the initial peel strength meets the requirements, but simply changing the POE layer cannot meet the use needs of the encapsulation film. The encapsulation film of Example 1 only adds silane tackifier to the EVA layer to graft EVA granules, and the initial and 3-month DH2000 peeling strengths after 4 months of placement are guaranteed; the encapsulation films of Example 2, Example 5, and Example 6 improve the EVA layer and the POE layer at the same time, and have the advantages of the encapsulation films of Example 1, Comparative Example 2, and Comparative Example 3. Therefore, the DH2000 peeling strengths of the encapsulation films of Example 2, Example 5, and Example 6 after 5 months and 4 months of placement are guaranteed, but the peeling strength after 5 months does not meet the requirements. The encapsulation films of Example 3 and Example 4 use silane tackifiers with higher carbon chains, which have better hydrophobic effects, so the DH2000 peeling strength after 5 months of placement can be guaranteed. In summary, the high-storage EPE film provided by the present invention has significant improvements in performance relative to conventional EPE films.
[0089] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example.
[0090] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.
Claims
1. A high storage type EPE film, characterized in that: include: A first EVA layer, a POE layer, and a second EVA layer stacked in sequence along a thickness direction; The first EVA layer comprises the following raw materials and their weight proportions: 70-75 parts of EVA particles, 20-25 parts of silane tackifier grafted EVA granules, 0.5-1 parts of crosslinking agent, 0.4-1 parts of auxiliary crosslinking agent, 0.7-1.5 parts of acrylate, 0.1-0.5 parts of low molecular weight tackifier and 0.05-0.3 parts of light stabilizer; and / or The second EVA layer includes the following raw materials and their weight proportions: 70-75 parts of EVA particles, 20-25 parts of silane tackifier grafted EVA granules, 0.5-1 parts of crosslinking agent, 0.4-1 parts of auxiliary crosslinking agent, 0.7-1.5 parts of acrylate, 0.1-0.5 parts of low molecular weight tackifier and 0.05-0.3 parts of light stabilizer; Among them, the structure of the silane adhesion promoter is shown in the following formula I: (I) YR-SiX3, wherein Y is an active group participating in the free radical reaction, R is a linear hydrophobic carbon chain, the number of carbon atoms in the carbon chain is 5 to 8, and SiX3 is siloxane.
2. The high storage type EPE film according to claim 1, characterized in that: The silane adhesion promoter includes at least one of γ-methacryloxypentyltrimethoxysilane, γ-methacryloxyhexyltrimethoxysilane, γ-methacryloxyheptyltrimethoxysilane, 3-(methacryloxy)pentyltriethoxysilane, 3-(methacryloxy)hexyltriethoxysilane, 3-(methacryloxy)heptyltriethoxysilane, vinylpentyltrimethoxysilane, vinylhexyltrimethoxysilane and vinylheptyltrimethoxysilane.
3. The high storage type EPE film according to claim 1, characterized in that: The preparation method of the silane tackifier grafted EVA granules is as follows: after the initiator, the catalyst, the silane tackifier and the EVA particles are metered, fully mixed and absorbed, the materials are added, extruded, uniformly sheared, and cooled to obtain the finished product.
4. The high storage type EPE film according to claim 1, characterized in that: The POE layer includes raw materials and weight portions as follows: 70-80 parts of POE particles, 20-30 parts of POE granules grafted with silane tackifiers, 0.5-1.2 parts of crosslinking agents, 0.6-1 parts of auxiliary crosslinking agents, 0.2-0.5 parts of acrylates, 0.2-0.5 parts of low molecular weight tackifiers, 0.05-0.2 parts of silane tackifiers and 0.05-0.2 parts of light stabilizers.
5. The high storage type EPE film according to claim 4, characterized in that: The preparation method of the silane-silane tackifier grafted POE granules is as follows: the initiator, the catalyst, the silane tackifier and the POE particles are metered, fully mixed and absorbed, added, extruded, uniformly sheared, and cooled to obtain the finished product.
6. The high storage type EPE film according to claim 1 or 4, characterized in that: The crosslinking agent is one or more of tert-butyl peroxy-2-ethylhexyl carbonate, tert-amyl peroxy-2-ethylhexyl carbonate, methyl ethyl ketone peroxide, benzoyl peroxide, di-tert-butyl peroxide and diisopropylbenzene hydroperoxide.
7. The high storage type EPE film according to claim 1 or 4, characterized in that: The auxiliary cross-linking agent is one or more of triallyl isocyanurate, triallyl cyanurate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, tripropylene glycol diacrylate, dipropylene glycol diacrylate and triethylene glycol methyl diacrylate.
8. The high storage type EPE film according to claim 1 or 4, characterized in that: The low molecular adhesive is one or more of γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, 3-(methacryloxy)propyltriethoxysilane, 3-(methacryloxy)propyltrimethoxysilane, vinyltrimethoxysilane and vinyltriethoxysilane.
9. The high storage type EPE film according to claim 1, characterized in that: The thickness of the first EVA layer is d1, wherein d1 satisfies: 200 μm≤d1≤220 μm; and / or The thickness of the POE layer is d2, wherein d2 satisfies: 190 μm≤d2≤210 μm; and / or The thickness of the second EVA layer is d3, wherein d3 satisfies: 200 μm≤d3≤220 μm.
10. A method for preparing a high storage type EPE film according to any one of claims 1 to 9, characterized in that: The steps include: The raw materials of the first EVA layer, the POE layer and the second EVA layer are mixed respectively, and after standing, the mixed mixture is extruded into a composite molten state film through a twin-screw and twin-die casting, and then cooled and formed.
11. A photovoltaic module, characterized in that: include: A front cover plate, a front packaging film, a battery layer, a back packaging film and a back cover plate stacked in sequence along the thickness direction; At least one of the front encapsulation film and the back encapsulation film is a high-storage type EPE film according to any one of claims 1 to 9, or a high-storage type EPE film prepared by the preparation method according to claim 10.